Determinants Of Conventional Bank Profitability: Is Covid-19 Matter? - Sholikha Oktavi Khalifaturofi'ah; Indra Listyarti; Ririn Poerwanti (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
This study delves into the determinants of profitability in conventional banks. This study uses a quantitative method to analyze the factors influencing bank profitability. This study uses balanced panel data using the fixed-effects model from 18 conventional banks from 2009 to 2021 in Indonesia. The results suggest that COVID-19 has a negative impact on profitability. Nevertheless, bank specifics such as capital and bank size positively influenced profitability, while efficiency significantly negatively influenced profitability. Moreover, this study delves into macroeconomic indicators, revealing their pronounced significance. Economic growth and interest rates emerged as substantial drivers, positively shaping bank profitability. Conversely, the exchange rate exerted a noteworthy negative influence on profitability. Bank stakeholders are expected to improve performance by increasing the bank's capital and assets. A bank should be able to increase its size through its total assets. Monetary policies, such as controlling interest and exchange rates, are found to be an important factor in determining banking profitability.